Strengthening Hydromet and Early Warning Services in Afghanistan : A Road Map - World Bank Group (World Bank, Washington, DC, 2018)
Hydrological and meteorological (hydromet) data collection and analysis in Afghanistan started in the late 1940s and mid-1950s, respectively. The hydrometric network expanded rapidly in the 1960s and 1970s, reaching a peak of 150 in 1980, and the meteorological network had a similar trajectory. Two decades of war, however, brought instability and insecurity that reduced public resources, capacities, collaboration, and coordination. The institutional framework governing weather, climate and hydrological (hydromet) services as well as early warning (EW) and disaster risk management (DRM) services did not escape these setbacks. In 1996, Taliban forces sacked the meteorology office, ruining equipment and destroying over 100 years of weather records. Hydroelectric production nearly ceased as turbines were destroyed, floodgates blown open, and transmission lines brought down. The civil war and its aftermath led to the degradation of traditional observation networks, prevalence of outdated and inefficient technologies, and lack of modern instruments and information and communication technology (ICT). The absence of forecasts and weather information reversed years of development gains in farming and civil aviation operations. In 1998, an Ariana Afghan Airlines flight in route from Kandahar to Kabul in bad weather crashed into a mountaintop, killing 45 people. From 1998 to 2004, a major drought forced nearly 1 million Afghans from their farms and herds into metropolitan areas, impacting half the agriculture land, killing 3 million livestock, and seriously depleting groundwater resources in Kabul and the Kabul Water Basin.